Continuous efforts to educate decision-makers at all levels on the nexus in Nepal - Phuyal, Surendra; Koirala, Sanju; Karki,Darshan; Mishra, Anuj (International Water Management Institute, 2024)
Experts and stakeholders working to ensure greater acceptance of the water–energy–food–ecosystems (WEFE) nexus approach in Nepal are calling for renewed efforts to get the WEFE nexus incorporated in government programs and policies.